Open-Book Final Examination: Do the Students Think it is Easier and Better for Them? - Anuar A.; Ibrahim Z.; Jamaluddin J.E. (Springer Science and Business Media Deutschland GmbH, 2025)
Assessment is always an important component in the teaching and learning process. The final examination is often carried out as a summative type of assessment to evaluate the student learning at the end of a course. Typically, final examination is conducted in a controlled environment ?close book? approach. The less common method is using the ?open book? approach. A study was conducted at Universiti Tenaga Nasional (UNITEN) to investigate the students? perception on open-book final examination, through a cross-sectional survey conducted among UNITEN students. The survey was conducted online between July 14, 2022, and August 8, 2022. Were number of respondents was 693 students, with 66.5% were male students, and 33.5% were female students. About half of the respondents think an open-book exam is easier (51.9% agree or strongly agree); and about two-thirds of the respondents think that they can get better results if the examination is conducted in open-book method (67.7% agree or strongly agree); and most of the respondents think that taking open-book examination is less stressful than closed-book examination (73.1% agree or strongly agree). Based on this survey, most students perceived that open-book examination is easier and better for them. ? The Author(s).